2014
DOI: 10.4161/15592316.2014.972864
|View full text |Cite
|
Sign up to set email alerts
|

Identification of transcription factors linked to cell cycle regulation inArabidopsis

Abstract: Cell cycle is an essential process in growth and development of living organisms consists of the replication and mitotic phases separated by 2 gap phases; G1 and G2. It is tightly controlled at the molecular level and especially at the level of transcription. Precise regulation of the cell cycle is of central significance for plant growth and development and transcription factors are global regulators of gene expression playing essential roles in cell cycle regulation. This study has uncovered TFs that are inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Moreover, the Arabidopsis GRAS‐type SCL28 transcription factor has been recently identified as controlling gene expression dynamics in the mitotic cell cycle [127]. Similarly, three AP2 genes have been upregulated in Arabidopsis during the G1 phase of the cell cycle [128].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the Arabidopsis GRAS‐type SCL28 transcription factor has been recently identified as controlling gene expression dynamics in the mitotic cell cycle [127]. Similarly, three AP2 genes have been upregulated in Arabidopsis during the G1 phase of the cell cycle [128].…”
Section: Resultsmentioning
confidence: 99%
“…TFs involved in cell cycle regulation/or stress response belong to AP2/EREBP, bZIP, C2H2, C3H, MYB, bHLH, HD‐ZIP, WRKY, NAC, MADS‐box, LOB, DOF, HB, GATA, HSF, YABBY, ABI3/VP1, and other TF families. The most overrepresented TFs in plants are members of the AP2/EREBP, C2H2, MYB, WRKY, and bHLH families (Dehghan Nayeri, 2014). The role of MYBs in trichome formation was reported by Zhou et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, in most case, we found that the expression level of genes related to cell mitosis is not affected by PMO application. This might be attributed to two reasons: 1) most of cell mitosis genes are constitutively expressed [58] and 2) PMO might affect these genes at the post transcription level which is of interest for future studies. Overall, our results suggest that PMO could be a good candidate to promote cell mitosis activities, especially under drought stress.…”
Section: Mn 3 O 4 Nanoparticles Alleviated Drought Inhibited Root Ape...mentioning
confidence: 99%